EIB Fraud Investigations Activity Report 2020 - European Investment Bank (European Investment Bank, 2021)
This Fraud Investigations Activity Report describes the activities of the Inspectorate General's Fraud Investigations Division (IG/IN) in 2020, giving an overview of IG/IN's work to prevent, detect, investigate and remedy Prohibited Conduct affecting EIB Group activities. In particular, the report provides: A chapter dedicated to the impact of the Covid-19 pandemic on IG/IN's investigations; Relevant statistics and analysis on the number of allegations received and investigations conducted; A number of internal and external case studies reflecting the range of allegations handled by investigators as well as the findings and lessons learned; An overview of the fraud detection tools and methodology developed by IG/IN as well as relevant case studies showcasing how on-the-ground Proactive Integrity Reviews are performed; An overview on deterrence and rehabilitation activities; and Information on the policy work undertaken by IG/IN, such as fraud and corruption training and awareness initiatives for EIB Group staff members, and continued efforts in outreach and global partnerships.